Associated Topics || Dr. Math Home || Search Dr. Math

### Arithmetic Progression

```
Date: 12/19/96 at 19:14:26
From: Sushant
Subject: Arithmetic progression

I am stuck on two problems involving arithmetic progression:

1. If (b+c-a)/a, (c+a-b)/b and (a+b-c)/c are in arithmetic
progression, show that 1/a, 1/b and 1/c are also in A.P.

2. If a+b+c is not equal to zero and (b+c)/a, (c+a)/b and (a+b)/c are
in A.P., show that 1/a, 1/b and 1/c are also in A.P.
```

```
Date: 12/19/96 at 20:25:59
From: Doctor Pete
Subject: Re: Arithmetic progression

Hi,

(1) Take the difference of the first two terms, (b+c-a)/a - (c+a-b)/b,
and set it equal to the difference of the last two terms,
(c+a-b)/b - (a+b-c)/c.  Simplify.  This will give a relation
between 1/a, 1/b, and 1/c which indicates that their successive
differences will also be the same.

If a + b + c = 0, then the statement is false (prove it!).

(2) This follows directly from the first problem -- they are the same.

-Doctor Pete,  The Math Forum
Check out our web site!  http://mathforum.org/dr.math/
```

```
Date: 12/19/96 at 21:03:25
From: Sushant
Subject: Arithmetic progression

```

```
Date: 12/21/96 at 03:15:40
From: Doctor Pete
Subject: Re: Arithmetic progression

1)  Let

x1 = (b+c-a)/a = (b+c)/a - 1,
x2 = (c+a-b)/b = (a+c)/b - 1,
x3 = (a+b-c)/c = (a+b)/c - 1.

Then consider the successive differences

x3 - x2 = (a+b)/c - 1 - (a+c)/b + 1 = (a+b)/c - (a+c)/b
= (b(a+b) - c(a+c))/(bc) = (ab + b^2 - ac - c^2)/(bc)
= (a(b-c) + b^2 - c^2)/(bc)
= (a(b-c) + (b+c)(b-c)/(bc)
= (a+b+c)(b-c)/(bc) ,
and
x2 - x1 = (a+c)/b - 1 - (b+c)/a + 1
= (a+b+c)(a-b)/(ab)

Since these must be equal if x1, x2, x3 are in arithmetic progression,
it follows that:

(a+b+c)(b-c)/(bc) = (a+b+c)(a-b)/(ab),

whereupon dividing by a+b+c (since it cannot be zero), we see:

(b-c)/(bc) = (a-b)/(ab)

whereupon separating the terms in the numerator gives:

1/c - 1/b = 1/b - 1/a

But if we consider the sequence y1 = 1/a, y2 = 1/b, and y3 = 1/c, this
implies that the successive differences y3 - y2 = y2 - y1, hence y1,
y2, y3 are in also in arithmetic progression, and we are done.

Note that in order for the problem stated to be true, we must have a,
b, c, and a+b+c nonzero.  It is clear that a, b, and c mustn't be
zero, but to see why their sum must also be nonzero, observe that if
it were zero, then:

x1 = (b+c-a)/a = (-2a)/a = -2
x2 = (c+a-b)/b = (-2b)/b = -2
x3 = (a+b-c)/c = (-2c)/c = -2

So x1, x2, x3 form a trivial arithmetic sequence of common difference
0 for *any* choice of a, b, c.  Hence the reciprocals 1/a, 1/b, 1/c
need not be in arithmetic progression.

The answer to problem 2 is obviously a direct result of problem 1, for
if a sequence x1, x2, x3 is arithmetic with common difference d, then
(x1)+n, (x2)+n, (x3)+n is also arithmetic with common difference d,
for any value of n.

-Doctor Pete,  The Math Forum
Check out our web site!  http://mathforum.org/dr.math/
```

```
Date: 12/21/96 at 22:38:41
From: Sushant
Subject: Re: Arithmetic progression

Thanks a lot. I am enlightened.
```
Associated Topics:
High School Basic Algebra
High School Sequences, Series

Search the Dr. Math Library:

 Find items containing (put spaces between keywords):   Click only once for faster results: [ Choose "whole words" when searching for a word like age.] all keywords, in any order at least one, that exact phrase parts of words whole words

Submit your own question to Dr. Math
Math Forum Home || Math Library || Quick Reference || Math Forum Search